Perencanaan Pengembangan Perpustakaan Digital di Sekolah Menengah Atas (SMA) Negeri 1 Padang - Andra Novrianto. S; Sufyarma M; Hadiyanto Hadiyanto; Irsyad Irsyad (Universitas Negeri Padang, 2020)
The school library as a source of information in schools, continues to experience changes and developments. The current era of public information openness, which is better known as the industrial revolution 4.0 also demands that school libraries make changes to follow this revolution. Most of the school libraries today still use conventional libraries. To change the condition of the library, various preparations are needed to do it. This research will discuss how to plan digital-based library development in a school environment. This article is written on the basis of research. The research was conducted in schools that previously led to digital-based libraries, researchers chose libraries at SMAN 1 Padang. This research is a descriptive study with qualitative methods. The data validity analysis method used source triangulation and technique triangulation. The results of data analysis show: 1) planning for the development of digital library facilities at SMAN 1 Padang still requires network development, computers and scanners, 2) planning for digital library development for digital collections also needs to be done, namely in the process of digitizing collections, 3) planning for developing management competencies Librarian information needs to be done, 4) planning to improve digital library services needs to be done, especially in improving library reference services, and 5) planning for library supervision needs to be maintained, because the library control planning has been done well.